2020
DOI: 10.1073/pnas.1919350117
|View full text |Cite
|
Sign up to set email alerts
|

The β-encapsulation cage of rearrangement hotspot (Rhs) effectors is required for type VI secretion

Abstract: Bacteria deploy rearrangement hotspot (Rhs) proteins as toxic effectors against both prokaryotic and eukaryotic target cells. Rhs proteins are characterized by YD-peptide repeats, which fold into a large β-cage structure that encapsulates the C-terminal toxin domain. Here, we show that Rhs effectors are essential for type VI secretion system (T6SS) activity in Enterobacter cloacae (ECL). ECL rhs− mutants do not kill Escherichia coli target bacteria and are defective for T6SS-dependent export of hemolysin-coreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 67 publications
(97 reference statements)
8
49
0
Order By: Relevance
“…In contrast to a strain expressing wild-type RhsA, strains expressing the D1324N or D1346N variants of the protein were unable to outcompete RhsA-sensitive recipient bacteria indicating that C-terminal autocleavage is required for T6SS-dependent killing by this effector (Figure 2C). These findings mirror what has been observed for T6SS-exported Rhs proteins in Aeromonas dhakensis and Enterobacter cloacae suggesting that toxin domain liberation is a universal property of Rhs effectors 18, 31 .…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…In contrast to a strain expressing wild-type RhsA, strains expressing the D1324N or D1346N variants of the protein were unable to outcompete RhsA-sensitive recipient bacteria indicating that C-terminal autocleavage is required for T6SS-dependent killing by this effector (Figure 2C). These findings mirror what has been observed for T6SS-exported Rhs proteins in Aeromonas dhakensis and Enterobacter cloacae suggesting that toxin domain liberation is a universal property of Rhs effectors 18, 31 .…”
Section: Resultssupporting
confidence: 86%
“…These findings mirror what has been observed for T6SS-exported Rhs proteins in Aeromonas dhakensis and Enterobacter cloacae suggesting that toxin domain liberation is a universal property of Rhs effectors 18,31 .…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Modularity is an important property of T6SSs, as it allows components to organize at multiple levels and evolve semiautonomously, preserving functionality while conferring flexibility ( 50 ). For example, RHS and specialized effectors, also in agrobacteria, allow for reshuffling of toxin domains downstream of a conserved sequence while maintaining functions necessary for T6SS assembly and activation ( 51 , 52 ). In addition, genes necessary for effector loading, a final checkpoint that regulates T6SS assembly and activation, are consistently clustered as a functional unit in vgrG loci ( 39 , 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…These authors also suggested that the T6SS-2 was implicated in biofilm formation and cell adherence and that it contributed to bacterial colonization of the mouse gut in vivo 41 . The finding on the system's functionality should be taken with caution, however, as Donato and colleagues showed that the T6SS-2 of E. cloacae strain ATCC 13047 was defective due to a large deletion and the insertion of an IS903 element, which led to the pseudogenization of several T6SS-2 genes (clpV2, vgrG3, PAAR, and tssF2) 42 . Notably, the sequence of the T6SS-2 cluster in the here-described sequencing data of strain DSM 30054/ATCC 13047 was 100% identical to the one previously reported (accession number CP001918 43 ), confirming these pseudogenes.…”
Section: Resultsmentioning
confidence: 99%